A Comparison Between The Chute And Grizzly System And The Slusher System At The Climax Mine - Robert Henderson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1944)
SEVERAL very interesting articles have been written on the caving system of mining, but most of these papers have dealt separately with the slusher system or the chute and grizzly system. In this paper, a comparison will be made of the two methods, both of which are being used at the Climax mine. The mine is on the Continental Divide, in central Colorado, at an altitude of approximately 11,500 ft. above sea level. The long, cold winters, characteristic of the high Rockies, create a number of operating problems not usually found in other mining areas. THE ORE BODY The Climax ore body is just east of the Mosquito fault. This structural deformation has brought the granite on the east against the sedimentary rocks on the west. The ore occurs in an intensely altered granite and schist around a silicified granite core. The ore is in a highly fractured zone of moderate silicification. The principal mineral, molybdenite, is found in these fractures. Barren dikes of granite porphyry cut through the ore body and core with no apparent regularity. The grade of the ore is fairly uniform and gradually decreases toward the footwall core and also into the hanging-wall granite. The footwall and hanging wall are determined entirely by assays. The ore body is roughly dome-shaped, with the apex truncated at the surface. It is covered to varying depths with talus. A horizontal section of the ore body on the Phillipson level appears as an annular ellipse surrounding the footwall core. The ring of ore varies in width from 300 ft. to as much as 800 ft. The north-south axis of the core is about 1200 ft. and the east-west axis is about 1800 ft. In the ore zone, the rock is sufficiently strong to maintain reasonably large openings, and openings larger than haulage drifts usually have to be supported. The ore is cut by a great many fractures and shears and breaks into rather large blocks when caved, necessitating considerable secondary blasting. The waste that overlies the ore body breaks relatively fine in comparison with the size of the blocks of the caved ore and tends to run through the broken ore in the cave, causing dilution unless the draw is carefully controlled. MINING SYSTEMS For several years the ore was mined by the chute and grizzly system, a system that differs from that used in other caving mines only in the size of openings and equipment. In the chute and grizzly system, main haulage laterals were driven along the footwall core and also along the